Desmoglein 2, but not desmocollin 2, protects intestinal epithelia from injury. Issue 6 (November 2018) - Gross, Annika; Pack, Lotta; Schacht, Gabriel; Kant, Sebastian; Ungewiss, Hanna; Meir, Michael; Schlegel, Nicolas; Preisinger, Christian; Boor, Peter; Guldiken, Nurdan; Krusche, Claudia; Sellge, Gernot; et al.
Abstract Desmosomes are the least understood intercellular junctions in the intestinal epithelia and provide cell–cell adhesion via the cadherins desmoglein (Dsg)2 and desmocollin (Dsc)2. We studied these cadherins in Crohn's disease (CD) patients and in newly generated conditional villin-Cre DSG2 and DSC2 knockout mice (DSG2ΔIEC ; DSC2ΔIEC ). CD patients exhibited altered desmosomes and reduced Dsg2/Dsc2 levels. The intestines of both transgenic animal lines were histopathologically inconspicuous. However, DSG2ΔIEC, but not DSC2ΔIEC mice displayed an increased intestinal permeability, a wider desmosomal space as well as alterations in desmosomal and tight junction components. After dextran sodium sulfate (DSS) treatment andCitrobacter rodentium exposure, DSG2ΔIEC mice developed a more-pronounced colitis, an enhanced intestinal epithelial barrier disruption, leading to a stronger inflammation and activation of epithelial pSTAT3 signaling. No susceptibility to DSS-induced intestinal injury was noted in DSC2ΔIEC animals. Dsg2 interacted with the cytoprotective chaperone Hsp70. Accordingly, DSG2ΔIEC mice had lower Hsp70 levels in the plasma membrane compartment, whereas DSC2ΔIEC mice displayed a compensatory recruitment of galectin 3, a junction-tightening protein. Our results demonstrate that Dsg2, but not Dsc2 is required for the integrity of the intestinal epithelial barrier in vivo.